ECOLOGICAL DIVERGENCE OF RABIES VIRUS - Р. А. Нуратинов (Юг России: экология, развитие, 2014)
Abstract. The results of monitoring of ecological divergence of rabies virus in dependence on natural selection during the migration in natural end anthropurgic focuses in the world and in Russia are elucidated in the work.